2010
DOI: 10.4103/0301-4738.62652
|View full text |Cite
|
Sign up to set email alerts
|

Solitary giant molluscum contagiosum presenting as lid tumor in an immunocompetent child

Abstract: We report the case of a three-year-old male child who presented with a single painless subcutaneously located upper lid mass of 1.2 × 1.5 cm with a central depression. The mass could be easily separated from overlying skin on complete excision biopsy and showed a never described before whitish brain like appearance consisting of multiple lobes and gyri, which histopathologically proved to be molluscum contagiosum (MC). Tests to investigate underlying immunodeficiency did not show any evidence of immunocompromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…7,10 Chemical agents such as silver nitrate, phenol and trichloroacetic acid, in resistant lesions in immunocompromised patients topical antiviral agent cidofovir (5%), intralesional or systemic interferon alpha, imiquimod (5%) cream, salicylic acid, glycolic acid, tretinoin, tazortene, 5% sodium nitrite co-applied daily with 5% salicylic acid topical preparations, podofilox, liquefied phenol, tretinoin, cantharidin, potassium hydroxide, adapelene 1% cream have been reported. 5,7,10 Oral treatment with cimetidine is another option. 7,10 A review of Cochrane database including 495 cases indicated that no therapy was universally and convincingly effective in treatment of MC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10 Chemical agents such as silver nitrate, phenol and trichloroacetic acid, in resistant lesions in immunocompromised patients topical antiviral agent cidofovir (5%), intralesional or systemic interferon alpha, imiquimod (5%) cream, salicylic acid, glycolic acid, tretinoin, tazortene, 5% sodium nitrite co-applied daily with 5% salicylic acid topical preparations, podofilox, liquefied phenol, tretinoin, cantharidin, potassium hydroxide, adapelene 1% cream have been reported. 5,7,10 Oral treatment with cimetidine is another option. 7,10 A review of Cochrane database including 495 cases indicated that no therapy was universally and convincingly effective in treatment of MC.…”
Section: Discussionmentioning
confidence: 99%
“…For faster resolution, many treatment modalities such as cryotherapy, extirpation and cauterization of base, topical chemical and antiviral agents, and oral cimetidine have been used. [3][4][5] …”
Section: Introductionmentioning
confidence: 98%
“…52 The most common treatment for ocular and periocular molluscum infections is surgical excision of the lesions, which has generally led to rapid and dramatic resolution of the disease. [52][53][54] The concurrent conjunctivitis has been frequently observed to resolve simultaneously with the clearance of the molluscum lesions, which provides further evidence that conjunctivitis occurs as a secondary disease. 52 …”
Section: Molluscum In Adultsmentioning
confidence: 95%
“…Giant MC with atypical sites such as the eyelid and nipple. 5,12,13 Though MCV affects any group, children are found to be more commonly affected by this virus.…”
Section: Discussionmentioning
confidence: 99%